Preparation of Primary Myogenic Precursor Cell/Myoblast Cultures from Basal Vertebrate Lineages - Froehlich, Jacob Michael (MyJove Corporation, 2014)
Due to the inherent difficulty and time involved with studying the myogenic program in vivo, primary culture systems derived from the resident adult stem cells of skeletal muscle, the myogenic precursor cells (MPCs), have proven indispensible to our understanding of mammalian skeletal muscle development and growth. Particularly among the basal taxa of Vertebrata, however, data are limited describing the molecular mechanisms controlling the self-renewal, proliferation, and differentiation of MPCs. Of particular interest are potential mechanisms that underlie the ability of basal vertebrates to undergo considerable postlarval skeletal myofiber hyperplasia (i.e. teleost fish) and full regeneration following appendage loss (i.e. urodele amphibians). Additionally, the use of cultured myoblasts could aid in the understanding of regeneration and the recapitulation of the myogenic program and the differences between them. To this end, we describe in detail a robust and efficient protocol (and variations therein) for isolating and maintaining MPCs and their progeny, myoblasts and immature myotubes, in cell culture as a platform for understanding the evolution of the myogenic program, beginning with the more basal vertebrates. Capitalizing on the model organism status of the zebrafish (Danio rerio), we report on the application of this protocol to small fishes of the cyprinid clade Danioninae. In tandem, this protocol can be utilized to realize a broader comparative approach by isolating MPCs from the Mexican axolotl (Ambystomamexicanum) and even laboratory rodents. This protocol is now widely used in studying myogenesis in several fish species, including rainbow trout, salmon, and sea bream(1-4).